OP0241 Efficacy of tocilizumab in takayasu arteritis: multicenter french retrospective study of 46 patients. (12th June 2018) - Mekinian, A; Resche-Rigon, M.; Comarmond, C.; Soriano, A.; constans, J.; alric, P.; Jego, P.; Bussato, F.; Dhote, R.; lazaro, E.; Kone pault, I.; Landron, C.; et al.
Abstract : Background: Objectives: We report the long term outcome of 46 TA patients treated with tocilizumab, describe the factors of response and compare the vascular event free survival to DMARDs. Methods: retrospective nationwide french study Results: We observed a decrease in the NIH scale; in C-reactive protein levels and in daily prednisone dose at 3 and 6 months, respectively; p<0.0001) under tocilizumab. The overall tocilizumab failure free survival was 81% [95% CI: 0.7 to 0.95], 72% [95% CI: 0.55 to 0.95] and 48% [95% CI: 0.2 to 0.1] at 12, 24 and at 48 months, respectively. The presence of constitutional symptoms at the time of tocilizumab initiation (hazard ratio 5.6 [95% CI: 1.08 to 29], p=0.041), C-reactive protein level (hazard ratio 1.16 [95% CI: 1.01 to 1.31] for every 10 mg/L, p=0.003) were significantly associated with tocilizumab-failure-free survival. The incidence of vascular complications of TA decreased significantly under tocilizumab compared to DMARDS therapy. Conclusions: This nationwide study shows that tocilizumab may reduce the incidence of vascular complications in TA. Disclosure of Interest: None declared